Returning individual research results to participants: Values, preferences, and expectations - Denise A. Kent; Michelle Villegas-Downs; Marina Del Rios; Michael Freedman; Jerry A. Krishnan; Martha G. Menchaca; Crystal L. Patil; Jenny Sculley; Nathan Tintle; Lynn B. Gerald (Journal of Clinical and Translational Science, 2024)
Abstract